2021
DOI: 10.1177/21514593211002164
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Hidden Blood Loss in Elderly Cervical Spondylosis Patients With Anterior Cervical Discectomy Fusion and Influencing Factors

Abstract: Introduction: To analyze the perioperative hidden blood loss (HBL) and its influencing factors in elderly cervical spondylosis patients treated with anterior cervical discectomy fusion (ACDF). Materials and Methods: From January 2017 to December 2018, 128 elderly cervical spondylosis patients (age > 65 y) treated with ACDF were selected. The patients’ height, weight, duration of symptoms, previous medical history and other basic information were routinely recorded. The hemoglobin (Hb), hematocrit (Hct) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 29 publications
5
18
0
Order By: Relevance
“…Among the independent risk factors, we found that sex had an important effect on perioperative HBL in PETD. Male patients had higher HBL in this study, which was similar to the results of Wen et al’s study16 and Cai et al’s study12 of HBL in anterior cervical discectomy fusion surgery. One reasonable explanation was that male usually have a greater baseline level of Hb and body weight 31.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Among the independent risk factors, we found that sex had an important effect on perioperative HBL in PETD. Male patients had higher HBL in this study, which was similar to the results of Wen et al’s study16 and Cai et al’s study12 of HBL in anterior cervical discectomy fusion surgery. One reasonable explanation was that male usually have a greater baseline level of Hb and body weight 31.…”
Section: Discussionsupporting
confidence: 92%
“…One reasonable explanation was that male usually have a greater baseline level of Hb and body weight 31. At the same time, the muscle content of male is often larger than that of female, greater muscle and soft tissue damage during PETD may result in more HBL 12. Our study also found that higher disk degeneration grade is also an independent risk factor for increased HBL.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Furthermore, we found that operative time was also an important risk factor in HBL, which is similar to the results of previous studies. 19 , 20 The reason may be that longer operative time usually means greater surgical damage, resulting in increased residual blood loss in the postoperative dead space. At the same time, a longer operative time will lead to a more severe postoperative inflammatory response, which will further aggravate hemolysis.…”
Section: Discussionmentioning
confidence: 99%